2014
DOI: 10.1371/journal.pone.0099163
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr Virus-Encoded Small RNAs (EBERs) Are Present in Fractions Related to Exosomes Released by EBV-Transformed Cells

Abstract: Epstein-Barr virus (EBV) is an oncogenic herpesvirus associated with a number of human malignancies of epithelial and lymphoid origin. However, the mechanism of oncogenesis is unclear. A number of viral products, including EBV latent proteins and non-protein coding RNAs have been implicated. Recently it was reported that EBV-encoded small RNAs (EBERs) are released from EBV infected cells and they can induce biological changes in cells via signaling from toll-like receptor 3. Here, we investigated if these abun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
85
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(85 citation statements)
references
References 59 publications
0
85
0
Order By: Relevance
“…Although EBER-La complexes may be released in a vesicle-independent manner, we did not detect La in exosomes by proteomics or by Western blotting (9). We used sucrose densitybased purification of exosomes, which may explain why we do not detect La in exosomes preparations (23). In addition, in EBVinfected LCLs, but not in EBV − control cells, inhibiting small RNA sorting raises IFNB1 transcription (Fig.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Although EBER-La complexes may be released in a vesicle-independent manner, we did not detect La in exosomes by proteomics or by Western blotting (9). We used sucrose densitybased purification of exosomes, which may explain why we do not detect La in exosomes preparations (23). In addition, in EBVinfected LCLs, but not in EBV − control cells, inhibiting small RNA sorting raises IFNB1 transcription (Fig.…”
Section: Discussionmentioning
confidence: 80%
“…Indeed, chronic activation of antiviral immunity by erroneous detection of extracellular RNA drives autoimmunity in predisposed individuals (20). Although binding of proinflammatory EBERs to cytoplasmic sensors has been reported in vitro (9)(10)(11)(12), there is little evidence that this may occur in latently infected B cells in a physiologically relevant context (21), but there are multiple indications that EBERs are secreted from infected cells (9,22,23).…”
Section: Significancementioning
confidence: 99%
“…In this study we identified 1041 miRNAs altogether in the extracellular vesicle and cell samples studied, which are more than most array systems would detect. [22][23][24][25][26][27]42,43 Further, comparison among expression of miRNAs is possible with deep sequencing approaches, if the absolute number of copies in the sample can be quantified. 44 In this study, by using the Quantile normalization method for all samples, miRNA expression showed positive relationship between the samples, although many detected miRNA are unique in the different subsets of vesicles ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20][21] Importantly, many small RNAs are released in the extracellular environment as EV cargo, which has been specifically documented for the exosomes. [22][23][24][25][26][27] Importantly, many cellular RNAs, including miRNAs are detected in the extracellular space, especially in extracellular vesicles. 28,29 Currently, extracellular RNA communication is also considered to be putatively important in animals, with important implications for biology, disease and medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Further studies are required to investigate and validate their roles in promoting EBV-derived cancers. The occurrence of exosomes carrying mRNAs encoding for oncogenic EBV proteins such as LMP1, LMP2, EBNA1 and EBNA2 [46,47] as well as EBERs has also been documented (Figure 1). While the functions of these RNAs in the EBV-infected cancer cells are well-described, whether or not the exosomal RNAs are transferable to the recipient cells and exert their tumorigenic effects remains a question.…”
Section: Novel Implications Of Exosomes In Diagnosis and Treatment Ofmentioning
confidence: 92%